2012
DOI: 10.1007/s10805-012-9156-5
|View full text |Cite
|
Sign up to set email alerts
|

Cheating on Exams in the Iranian EFL Context

Abstract: The present study aimed at investigating the status of cheating on exams in the Iranian EFL context. One hundred thirty two university students were surveyed to this end. They were selected through convenient sampling. The results indicated that cheating is quite common among the Iranian language students. The most important reasons for this behavior were found to be "not being ready for the exam", "difficulty of the exam", "lack of time to study" and "careless and lenient instructors". The study also indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 63 publications
(101 reference statements)
4
17
1
17
Order By: Relevance
“…In this regard, assignments not read and lack of care taken by the overseers during the exam was mentioned among the reasons for cheating. This finding concurs with similar findings reported in the literature such as the relationship between doing assignments by copying from the internet and some instructor-based variables (Ersoy, 2014;Ersoy & Özden, 2011) and irresponsible behaviors of overseers (Ahmadi, 2012).…”
Section: Results Discussion and Suggestionssupporting
confidence: 92%
See 2 more Smart Citations
“…In this regard, assignments not read and lack of care taken by the overseers during the exam was mentioned among the reasons for cheating. This finding concurs with similar findings reported in the literature such as the relationship between doing assignments by copying from the internet and some instructor-based variables (Ersoy, 2014;Ersoy & Özden, 2011) and irresponsible behaviors of overseers (Ahmadi, 2012).…”
Section: Results Discussion and Suggestionssupporting
confidence: 92%
“…Bu kapsamda ödevlerin okunmaması, gözetmenlerin sınavlar sürecince özenli olmamasının kopya çekme nedenleri arasında belirtildiği görülmüştür. Araştırmanın bu sonucu öğretmen adaylarının internetten kopya odev yapmaları ile oğretim elemanı kaynaklı kimi değişkenlerin ilişkili olduğu (Ersoy, 2014;Ersoy ve Özden, 2011) ve gözetmenlerin sorumlu davranmadığı (Ahmadi, 2012) bicimindeki araştırma sonuçlarıyla da örtüşmektedir.…”
Section: Kişisel öZelliklerunclassified
See 1 more Smart Citation
“…9, No. 2;2016 Because of the importance of academic integrity in education and the pervasiveness of cheating behaviors among students of all ages and levels, recent researchers have shown interest in investigating the reasons behind the tendency of students to cheat (Ahmadi, 2012;Murdock & Anderman, 2006). It is believed that preventive techniques cannot be fruitful if real reasons of cheating are not examined and follow up actions are not appropriately taken.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the review of the related literature indicated that although many of those issues have been investigated in Iranian higher education contexts (e.g. Ahmadi, 2012Ahmadi, , 2014Amiri, Khamesan and Ayati, 2012;Khoshsaligheh, Mehdizadkhani and Keyvan, 2017;Rezanejad and Rezaie;, the issue of how Iranian TEFL professors' views towards plagiarism is reflected in their course syllabuses has been ignored. In order to get a better picture of the phenomena, the following research questions were addressed: …”
Section: Literature Reviewmentioning
confidence: 99%